Degree of Existence and Ontology of Virtual Reality in the Framework of Mulla Sadra’s Metaphysics of Wujūd - Mashayla Billups; Adedoyin Adekunle; Mohammad Hossein Zadeh; Nafise Mostafavi (Al-Qarawiyyin: Jurnal Ilmu Ushuluddin, 2026)
The development of virtual reality, the metaverse, and immersive digital environments raises ontological questions about the existence of virtual entities that are neither entirely material nor reducible to mere mental constructions. Contemporary digital ontology approaches still tend to be trapped in the dichotomy of real-pseudo and material-symbolic, so they are unable to explain the relational and hierarchical gradation of virtual reality’s existence. This study aims to reconstruct the ontological status of virtual reality through the framework of Mulla Sadra’s metaphysics of wujūd, emphasizing the concepts of aṣālat al-Wujūd, tashkīk al-Wujūd, the ontology of khayāl, and ḥarakah jawhariyyah. This research is a literature study with a philosophical-analytical approach, grounded in ontological analysis and the conceptual reconstruction of Mulla Sadra’s primary texts, as well as contemporary literature on the philosophy of technology and digital ontology. The results show that virtual reality has a real, derivative status as existence, with a weaker intensity of wujūd than that of external reality. From the perspective of tashkīk al-Wujūd, virtual reality is understood as a relational mode of existence that depends on the material substrate of technology, digital information systems, and the subject’s intentionality. The ontology of khayāl situates virtual reality as an intermediate realm between materiality and intellectuality, while ḥarakah jawhariyyah describes its dynamic, continuous existential transformation. This study confirms that Sadrian metaphysics offers a conceptual alternative to contemporary digital ontology and expands Islamic philosophy’s contribution to the study of modern philosophy of technology.